Preliminary screening of rice cultivars for tolerance to iron toxicity - Fageria, Nano Kumar; Barbosa Filho, Morel Pereira; Carvalho, José Ruy Porto; Rangel, Paulo Hideo Nakano; Cutrim, Veridiano dos Anjos (Pesquisa Agropecuaria Brasileira, 2014)
Iron toxicity has becoming a serious problem in several regions of irrigated rice in Brazil. Two greenhouse experiments were conducted to identify rice germplasm tolerant to iron toxicity. One hundred and fifteen cultivars lines were screened for iron tolerance in nutrient solution. Variable iron concentrations - 0.5, 2.5, 10, 20, 40, 60, 80 and 100 ppm - were used in the first experiment, and 2.5, 20,40 and 100 ppm in the second one. The effect of the iron on the dry matter production of the tops and roots was determined. Dry matter of tops showed higher sensibility to iron toxicity in comparation to roots weight. Hence, a reduction in dry matter of tops was calculated at higher levels of iron in relation to lower level of iron. Based on this yield reduction, cultivars/lines were classified as tolerant, moderately tolerant, moderately susceptible and susceptible to iron toxicity. These results showed that rice cultivars differ largely in their tolerance to iron toxicity under the conditions they were evaluated.